Implementation Of Health Protocol In Preventing The Spread Of The Covid 19 Virus - Rahmadhani Fitri; Hendra Fahruddin Siregar; Adi Sastra Pengalaman Tarigan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Covid-19 is a positive single strain RNA virus that infects the respiratory tract. This virus spreads quickly, the only way is to prevent it. As time progressed, the conditions of transmission became more widespread and took many victims, ranging from adults, teenagers to children. This virus can attack anyone, this virus can also attack children with special needs. Children with special needs are children with special characteristics that are different from children in general without always showing mental, emotional, or physical disabilities. One of them is mental retardation. The more widespread the spread of the COVID-19 virus, the application and knowledge of health protocols must also touch the mentally retarded. This obstacle will affect them to adjust to the implementation of health protocols every day and homework for SLB C Muzdalifah to provide a safe place for students. Prepare students and teaching units in the implementation of New Normal Education. And Educate students so that they apply health protocols at all times. The approach method used in this community service is socialization through posters of health protocols and placement of hand sanitizers. Information on preventing the spread of covid 19 through posters and placing hand sanitisers in the SLB C Muzdalifah area as a reminder and teaching regularity in implementing health protocols. This information is expected to become a habit in the New Normal.